Inhibition of the Platelet Reaction by a High Molecular Weight Phosphoglycoprotein Isolated from Human Platelet Plasma Membranes - Apitz-Castro, R; Fonseca, G; Michelena, V; Cruz, M R (Thrombosis and Haemostasis, 1981)
The effect of a phospho-glycoprotein (HMW-GP), obtained from human platelet plasma membranes, on the aggregation and secretion of human platelets was studied. Incubation of PRP with 4 to 16 μg/ml of HMW-GP results in inhibition of ADP-, Epinephrine-, Collagen-, and Thrombin-induced platelet aggregation. The effect is mainly reflected on the secondary wave of aggregation. The inhibitory effect is partially overcome by higher concentration of the inducers, however, even under these conditions, a clear tendency towards disaggregation is observed. 5HT release (Col-induced) is strongly decreased from 50% to 4.5. The inhibitory effect on Thrombin-induced aggregation is markedly dependent on external calcium, being maximal at 5 mM calcium. The HMW-GP does not bind ADP or Thrombin. Membrane conformation is markedly affected, as evidenced by the effect of HMW-GP on the iodination of surface polypeptides of intact platelets. It is suggested that interaction of HMW-GP with the platelet membrane blocks the signal(s) transmission that links stimulus to activation. The inhibition observed might just represent an experimental amplification of the endogenous modulatory function that has been proposed for this high molecular weight phosphoglycoprotein.
Keywords: Platelet inhibition; Membrane-bound glycoproteins